Inuit education in Alberta and Nunavik (Canada) - Daveluy, Michelle (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2009)
During the reorganisation of education in Nunavut that led to the passing of Bill 21 in 2009, reliance on curricula developed in other parts of Canada was mentioned and sometimes perceived as problematic. In this article, I describe how Inuit concerns have recently been integrated into education policies and programming developed by the Alberta government. To examine educational issues that concern Inuit students at southern schools, I have compared Alberta’s efforts and activities with those of the Kativik School Board in Nunavik (Northern Quebec) where the education system is trilingual with programs in Inuktitut, French, and English. The comparison shows how curriculum content, languages of instruction, and administrative control interrelate in the Canadian context. In particular, curricula seem to be more spiritually focused in Western Canada than in Nunavik or Nunavut.